2017
DOI: 10.1093/geroni/igx024
|View full text |Cite
|
Sign up to set email alerts
|

A Health Profile of Senior-Aged Women Veterans: A Latent Class Analysis of Condition Clusters

Abstract: Background and ObjectivesThis study characterizes the multiple morbidities experienced by senior-aged women Veterans so that the Veterans Health Administration (VHA) and other health care systems may be better prepared to meet the health care needs of this growing cohort.Research Design and MethodsUsing the VHA’s Corporate Data Warehouse, we conducted a retrospective observational study of the 38,597 female veteran patients who were at least 65 years old and received care in the VHA during 2013 and 2014. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The multimorbid patterns: "Metabolic and cardiovascular disorders"; "Cardiovascular disorders"; "Minimal chronic conditions"; "Neuropsychiatric and functional disorders"; and for women "Complex multimorbidity" were also found in other studies. 19,21,42,[44][45][46] We found six patterns that showed only minimal differences between sexes, and two patterns showed substantial differences in Figure 3 Age-adjusted odds ratios for differences in healthcare complexity the last year before an acute hospitalization between patients in the eight multimorbid patterns. disease patterns and was therefore labelled differently for women and men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multimorbid patterns: "Metabolic and cardiovascular disorders"; "Cardiovascular disorders"; "Minimal chronic conditions"; "Neuropsychiatric and functional disorders"; and for women "Complex multimorbidity" were also found in other studies. 19,21,42,[44][45][46] We found six patterns that showed only minimal differences between sexes, and two patterns showed substantial differences in Figure 3 Age-adjusted odds ratios for differences in healthcare complexity the last year before an acute hospitalization between patients in the eight multimorbid patterns. disease patterns and was therefore labelled differently for women and men.…”
Section: Discussionmentioning
confidence: 99%
“…41 We did not find a pattern that we could classify as "healthy" as other studies have. 21,[42][43][44][45] However, the population in our study was defined as acutely hospitalized older medical patients and therefore likely represents a more vulnerable group. The majority of our sample (23% for women and 25% for men) was classified into the "Minimal chronic conditions" pattern for both sexes and also had the lowest expected number of chronic conditions (2 for women and 2 for men).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced age amplifies the impact of certain conditions, such as hypertension, diabetes, and certain tumors. Some studies have suggested that cellular/physical degeneration and immune-related deterioration can be the cause of age-related disease conditions [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data are aggregated from individual hospital VistA systems into the VA CDW, where it is modeled and prepared for use . The VA National Data Services and other data stewards regulate the right to use the data.…”
Section: Methodsmentioning
confidence: 99%